2019
DOI: 10.1177/2051570719828687
|View full text |Cite
|
Sign up to set email alerts
|

Persuasion of voices: The effects of a speaker’s voice characteristics and gender on consumers’ responses

Abstract: Voices are present in most communications. Yet, the literature on voice persuasion is astonishingly limited and fragmented, focusing on certain voice characteristics (e.g. pitch), contexts, and providing mixed results. This research attempts to integrate the various constructs and mechanisms involved in voice persuasion as a result of the cross-fertilization of the disciplines having studied voice (psychoacoustics, cognitive psychology, anthropology, psycho-sociology, marketing, and politics). Study 1 manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
1
16
0
2
Order By: Relevance
“…Previous studies adopting the consumer perspective indirectly confirm our findings regarding the role of brand voice characteristicsgender (Wiener and Chartrand, 2014;Zoghaib, 2017), pitch (Zoghaib, 2017;Zoghaib, 2019), accent (Morales et al, 2012) and speed (MacLachlan, 1982) in the perception of specific brand personality traits (e.g. W&C).…”
Section: Human-like Brand Personality Traitssupporting
confidence: 87%
See 2 more Smart Citations
“…Previous studies adopting the consumer perspective indirectly confirm our findings regarding the role of brand voice characteristicsgender (Wiener and Chartrand, 2014;Zoghaib, 2017), pitch (Zoghaib, 2017;Zoghaib, 2019), accent (Morales et al, 2012) and speed (MacLachlan, 1982) in the perception of specific brand personality traits (e.g. W&C).…”
Section: Human-like Brand Personality Traitssupporting
confidence: 87%
“…As shown in Table 1, the most commonly analysed voice characteristics are time compression and speed (MacLachlan, 1982;Moore et al, 1986;Chattonadhyay et al, 2003;Megehee et al, 2003), pitch (Chattonadhyay et al, 2003;Wiener and Chartrand, 2014;Zoghaib, 2017;Zoghaib, 2019), gender (Whipple and McManamon, 2002;Wiener and Chartrand, 2014;Zoghaib, 2017) and accent (Morales et al, 2012). While these characteristics have mainly been studied in commercial advertising contexts focussed on traditional radio media, several interesting empirical results connected to branding outcomes have appeared such as brand recall, brand attitude and brand evaluation as well as perceptions in terms of warmth and competence (W&C).…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When someone cannot be seen, their voice becomes more important; this is the case for podcasts and sales calls, where speakers are physically invisible. The auditory cues of the speaker's voice are then critical for the listener's perception and engagement intention [14,15]. Auditory cues are those that can be heard but are not expressed in words.…”
Section: Introductionmentioning
confidence: 99%
“…As such cues can be particularly powerful in conveying gender [16] and personality traits (especially the individual's degree of extraversion or introversion) [17,18], research has largely focused on these two traits. However, studies have found varying results, depending on the characteristics and context [14].…”
Section: Introductionmentioning
confidence: 99%